PENINGKATAN SIKAP PERCAYA DIRIDAN HASIL BELAJAR MAPEL IPS MELALUI MODELPEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING (SFE) - Setiawati, Esti; Surono, Ari (Jurnal Sosialita, 2024)
This study aims to improve student learning outcomes in Mupel Social Studies learning through the Student Facilitator and Axpaining (SFE) Learning Model in Class V of Brondong State Elementary School, Bruno District, Purworejo Regency, Academic Year 2021/2022. This research is a Classroom Action Research (PTK) which was conducted in 2 cycles. Based on the results of this study it can be concluded that the application of the Student Facilitator and Explaining (SFE) learning model can increase students' self-confidence as evidenced from the pre-cycle with a good category of 26.19%, an increase in cycle I to 46.15%, and a cycle II increased to 65.38%, as well as the learning outcomes of students in social studies content in Class V as evidenced by the increase in the average student completeness of 26.92% in the pre-cycle, up to 57.69% in cycle I and increased again in cycle II of 88.46%. Therefore, the student facilitator and explaining learning model can be applied as an alternative in increasing students' self-confidence and learning outcomes.